2014
DOI: 10.1371/journal.pone.0093920
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Selectively Inhibits Mouse Bone Marrow Lymphoid Progenitor Cell Development In Vivo and In Vitro and Suppresses Humoral Immunity In Vivo

Abstract: It is known that exposure to As+3 via drinking water causes a disruption of the immune system and significantly compromises the immune response to infection. The purpose of these studies was to assess the effects of As+3 on bone marrow progenitor cell colony formation and the humoral immune response to a T-dependent antigen response (TDAR) in vivo. In a 30 day drinking water study, mice were exposed to 19, 75, or 300 ppb As+3. There was a decrease in bone marrow cell recovery, but not spleen cell recovery at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…2c, 2d). These findings are consistent with our previous studies showing the selective suppression of CFU-B in mouse BM following 30 day low level As +3 exposures [6]. …”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…2c, 2d). These findings are consistent with our previous studies showing the selective suppression of CFU-B in mouse BM following 30 day low level As +3 exposures [6]. …”
Section: Resultssupporting
confidence: 94%
“…Because we previously found that MMA +3 (an As +3 metabolite) may be responsible for the toxicity of As +3 on BM in vivo [6], we investigated possible interaction of MMA +3 with DBC or DBC-diol in in vitro cultures, using one concentration (5 nM) that was previously establshed to be minimally toxic to the BM and another at a ten times lower concentration (0.5 nM). Both concentrations of MMA +3 suppressed CFU-B formation in mouse BM (Fig 3b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations